Istilah-Istilah dan Konsep Media, Media Pendidikan, Alat-Alat Pandang-Dengar, Teknologi Pendidikan, dan Teknologi Pengajaran - Alwiah Alsagoff, Sharifah (Penerbit Universiti Sains Malaysia, 1979)
This paper attempts to clarify the various concepts and terminologies pertaining to instructional technology. It traces the beginnings of media from its use in the form of clay tablets during the scribal age to present day usage of the terms media, educational media, instructional media, audio-visual aids, educational technology and instructional technology. The paper also explores the development and refinement of the above concepts and terminologies. A rationale for the establishment of instructional technology as a discipline is also attempted.